Inflammatory Cardiomyopathy: A Current View on the Pathophysiology, Diagnosis, and Treatment - Krejci, Jan; Mlejnek, Dalibor; Sochorova, Dana; Nemec, Petr (BioMed research international, 2016)
Inflammatory cardiomyopathy is defined as inflammation of the heart muscle associated with impaired function of the myocardium. In our region, its etiology is most often viral. Viral infection is a possible trigger of immune and autoimmune mechanisms which contributed to the damage of myocardial function. Myocarditis is considered the most common cause of dilated cardiomyopathy. Typical manifestation of this disease is heart failure, chest pain, or arrhythmias. The most important noninvasive diagnostic method is magnetic resonance imaging, but the gold standard of diagnostics is invasive examination, endomyocardial biopsy. In a significant proportion of cases with impaired left ventricular systolic function, recovery occurs spontaneously in several weeks and therefore it is appropriate to postpone critical therapeutic decisions about 3-6 months after start of the treatment. Therapy is based on standard heart failure treatment; immunosuppressive or antimicrobial treatment may be considered in some cases depending on the results of endomyocardial biopsy. If severe dysfunction of the left ventricle persists, device therapy may be needed.
Keywords: Biopsy; Humans; antiflogistika; myokarditida; biopsie; srdeční resynchronizační terapie; Cardiac Resynchronization Therapy; Cardiomyopathies; Anti-Inflammatory Agents; Anti-Bacterial Agents; výsledek terapie; Evidence-Based Medicine; medicína založená na důkazech; antibakteriální látky; kardiomyopatie; lidé; Treatment Outcome; Myocarditis